Implementation of Hepatitis B Screening Into Routine Antenatal Care to Prevent Mother-to-Child Transmission in Rural Western Uganda - Thahir, Sahal; Muhindo, Enid; Turigye, Brian; Kabagambe, Kenneth; Thompson, Peyton; Mulogo, Edgar M.; Boyce, Ross M. (In Open Forum Infectious Diseases, 2023)
In rural Uganda where birth dose vaccination for hepatitis B is not routine, we implemented a pilot program for preventing mother-to-child transmission that effectively identified women with high-risk hepatitis B virus (HBV) infection and started antiviral treatment during pregnancy. Further work is required to enhance antiviral adherence through delivery to ensure effective prevention of vertical HBV transmission.
Keywords: HBV; PMTCT; Tenofovir; vertical transmission